2022
DOI: 10.1111/jth.15883
|View full text |Cite
|
Sign up to set email alerts
|

The Khorana score and venous and arterial thrombosis in patients with cancer treated with immune checkpoint inhibitors: A Danish cohort study

Abstract: Background:Thrombosis is common among patients with cancer. Primary thromboprophylaxis guided by the Khorana score is endorsed by guidelines but recommendations rely mainly on data from patients treated with chemotherapy.Objectives: To explore if the Khorana score could risk stratify patients with cancer treated with immune checkpoint inhibitors according to risk of venous and arterial thrombosis.Patients/Methods: The study population and Khorana score were defined using administrative Danish health registries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The Khorana model has been extensively validated and employed in clinical settings, and the Vienna model has been reported as applicable for predicting VTE risk across various malignancies. 28 , 29 However, these models incorporate the location of the malignancy as one of the risk factors, despite the fact that the VTE risk varies considerably across different tumor sites, and the underlying mechanisms differ significantly. The use of such predictive models may obscure the predictive influence of certain risk factors on specific tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The Khorana model has been extensively validated and employed in clinical settings, and the Vienna model has been reported as applicable for predicting VTE risk across various malignancies. 28 , 29 However, these models incorporate the location of the malignancy as one of the risk factors, despite the fact that the VTE risk varies considerably across different tumor sites, and the underlying mechanisms differ significantly. The use of such predictive models may obscure the predictive influence of certain risk factors on specific tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis in ICI patients was evaluated in three Danish population cohort studies. 8,19,20 Two reported both ATE and VTE, 19,20 whereas one reported only VTE. 8 These studies reported a 2-4% VTE rate at 6 months and a 4-7% rate at 12 months, lower than retrospective studies.…”
Section: Incidence Of Venous Thromboembolism and Arterial Thromboembo...mentioning
confidence: 99%
“…Its value in prediction in an immunotherapy-only cohort has not been fully evaluated. Some studies found KS to predict for risk of VTE 18,20,45 whereas others did not. 1,24,26,42,[47][48][49][50][51]…”
Section: Risk Factorsmentioning
confidence: 99%
“…In addition to retrospective cohort studies, three Danish population cohort studies reported the incidence of thrombosis in patients on ICIs ( Table 3 ) [ 43 , 44 , 45 ]. It is interesting to note that the rates of thrombosis appear to be numerically lower in the population studies compared to the above-mentioned retrospective studies, with 6-month VTE rate of 2–4% and 4–7% at 12 months.…”
Section: Incidence Of Thrombosis In Patients Receiving Immune Checkpo...mentioning
confidence: 99%
“…As the development of the Khorana score predated ICIs, whether it can accurately predict thrombosis in patients receiving ICIs remains controversial as studies have shown mixed results. Most studies did not find the Khorana score to carry sufficient predictivity in this population [ 18 , 23 , 29 , 31 , 32 , 33 , 35 , 36 , 37 ], while a few studies did [ 27 , 45 , 46 ].…”
Section: Risk Factors Of Thrombosis In Patients On Immune Checkpoint ...mentioning
confidence: 99%